Collaborative Governance in the Regency Development Plan (Study in Tangerang District, Banten Provincy, 2021) - Slamet Budhi Mulyanto; Djoehermansyah Djohan; Mansyur Mansyur; Kusworo Kusworo (Budapest International Research and Critics University, 2022)
The Regional Government of Tangerang district carries out development through the planning process discussed in the Musrenbang. During the Covid-19 pandemic, budget diversion was prioritized for health care. So that other sectors which are also a priority are not implemented both in quality and quantity. The purpose of this study is to determine the mechanism of the exclusive planning process on the quality of planning, to analyze the differences between exclusivity and inclusivity and to build an inclusive planning model in collaborative governance (CG) as a reflection of equitable development planning and achieve people's welfare. The research method uses the basic theory of Collaborative Governance (CG) by Ansell and Gash in the development planning process. The implementation domains are participatory, inclusiveness, synergy, transparency as measured by commitment, synchronization, control and sanctions in favor of the people, supported by the theory of Government Science and the triple helix's theory. Collecting data by interview method, questionnaires, secondary data and observation. Processing of data with a qualitative approach supported descriptive statistics. This research shows that the government domain is still very dominant, while other actors have low participation and tend to be formal. The synergy of the actors is not optimal. The transparency trail is only accessible to an exclusive group. Thus, commitment is only made by the dominant group, access to control of other actors is closed and not involved when planning changes occur, there are no sanctions, so that the quality of planning does not meet the target. There is no official dialogue forum initiated by the government as a forum for discussing development planning by actors. Based on these conditions, the proposed collaborative governance model is to prepare a forum (dialogue forum) that functions as a participatory implementation of actors to answer problems in the development planning process with a commitment to achieve people's welfare.